Pengaruh Supervisi, Absensi Fingerprint, dan Budaya Organisasi terhadap Disiplin Kerja pada PT XYZ - Hafriz Rifki Hafas (Universitas Harapan Medan, 2020)
Supervision, fingerprint attendance and organizational culture are motivations to improve employee work discipline in an organization. Work discipline is something that must be applied in every employee. Employee awareness is required by complying with applicable regulations. Regulations are needed to provide guidance and counseling for employees in creating good order in the organization. Apart from that, the agencies themselves must endeavor so that the regulations are clear, easy to understand and apply to all employees. The population in this study is all employees who work at PT XYZ. The number of samples in this study were 89 respondents. Data were collected using a questionnaire. The data is tested using validity and reliability tests, and the data must fulfill the elements of the classical assumption test. Furthermore, the data analysis test was carried out using multiple linear regression, normality test, multicolinearity test and heteroscedasticity test. The results of this study indicate that supervision, fingerprint attendance and organizational culture on work discipline at PT XYZ. Supervision variables, fingerprint attendance and organizational culture are variables that significantly influence work discipline.